2017
DOI: 10.1016/j.celrep.2017.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Dysfunction Caused by Consumption of a High-Fat Diet

Abstract: SUMMARY Obesity is a major human health crisis that promotes insulin resistance and, ultimately, type 2 diabetes. The molecular mechanisms that mediate this response occur across many highly complex biological regulatory levels that are incompletely understood. Here, we present a comprehensive molecular systems biology study of hepatic responses to high-fat feeding in mice. We interrogated diet-induced epigenomic, transcriptomic, proteomic, and metabolomic alterations using high-throughput omic methods and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 68 publications
7
48
0
Order By: Relevance
“…A comprehensive multiomics study identified hepatocyte apoptosis as a key early signaling event in high‐fat diet‐induced NASH in mice . In keeping with this observation, mice deficient in apoptosis are protected from NASH .…”
Section: Steatosis and Lipotoxicitymentioning
confidence: 70%
“…A comprehensive multiomics study identified hepatocyte apoptosis as a key early signaling event in high‐fat diet‐induced NASH in mice . In keeping with this observation, mice deficient in apoptosis are protected from NASH .…”
Section: Steatosis and Lipotoxicitymentioning
confidence: 70%
“…To determine whether the in vivo effects of high‐fat diet (HFD) on mouse livers would mimic the in vitro effects of saturated fatty acids on hepatocytes, we used an established DIO model in C57BL/6J mice that has been shown to mirror hepatic dysfunction and signal transduction changes observed in patients (Collins et al , ; Soltis et al , ). Using a staggered HFD start to obtain an age‐matched end‐point, male mice were fed a normal chow diet (NC) or HFD for 6 or 16 weeks before euthanasia, liver resection, and analysis of the hepatic proteome and pTyr changes by LC‐MS/MS (Fig EV2A).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins associated with lipid metabolism, transport, and ß‐oxidation included apolipoproteins, fatty acid binding proteins, and mitochondrial proteins [e.g., acetyl‐CoA acetyltransferase ACAT1 (THIL), acyl‐CoA dehydrogenase (ACADM); Fig D, left panel], whereas a large number (> 20) of cytochrome P450 family members was in the pool of proteins downregulated in HFD (Fig D, right panel). We assessed the general reliability of our data by benchmarking it against previously published liver proteomes (Ghose et al , ; Benard et al , ; Liu et al , ; Soltis et al , ; Krahmer et al , ). Enrichment of the top GO terms in the up‐ and downregulated sets are consistent with these reports, and, despite stringent protein filters which reduced the number of quantified proteins from ~5,200 to ~4,400, our protein numbers are well within the range of those studies (950–6,000).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations